2011
DOI: 10.1089/hum.2010.069
|View full text |Cite
|
Sign up to set email alerts
|

α-Galactosidase A Expressed in the Salivary Glands Partially Corrects Organ Biochemical Deficits in the Fabry Mouse Through Endocrine Trafficking

Abstract: Fabry disease is caused by an X-linked deficiency of the lysosomal enzyme α-galactosidase A (GLA) and has been treated successfully with enzyme replacement therapy (ERT). Gene therapy has been proposed as an alternative to ERT due to the presumed advantages of continuous, endogenous production of the therapeutic enzyme. GLA production in the liver and its therapeutic efficacy in the Fabry mouse have been demonstrated previously with various viral vector systems. In consideration of the potential advantages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…Therefore, local delivery of drugs may be advantageous, as the salivary tissue could be targeted without widespread immunosuppression. Accordingly, salivary duct cannulation is an efficacious approach in animal models and further studies are needed to determine whether this approach is feasible for SS patients [161, 162]. Thus, therapeutics that target local or systemic innate immune hyperactivity will likely result in improved patient management and amelioration of SS disease.…”
Section: Therapeutic Approaches Targeting Innate Immunity May Be Ementioning
confidence: 99%
“…Therefore, local delivery of drugs may be advantageous, as the salivary tissue could be targeted without widespread immunosuppression. Accordingly, salivary duct cannulation is an efficacious approach in animal models and further studies are needed to determine whether this approach is feasible for SS patients [161, 162]. Thus, therapeutics that target local or systemic innate immune hyperactivity will likely result in improved patient management and amelioration of SS disease.…”
Section: Therapeutic Approaches Targeting Innate Immunity May Be Ementioning
confidence: 99%
“…Salivary gene delivery has been shown to be useful or potentially useful for the repair [28,29] and prevention [30–32] of radiation damage, the treatment of Sjögren’s syndrome [3335], and gene therapeutics (pharmacological applications) directed at both upper gastrointestinal tract [5,36] and systemic [6,7,23,37] conditions. Additionally, salivary gland gene delivery has been useful for asking biological questions in vivo [3841], as well as for creating novel models of disease [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…The report by Kagami et al [58] unequivocally demonstrated that both the rat parotid and submandibular glands could secrete a transgenic protein, in this case human α1-antitrypsin, into the bloodstream, while the report by He et al [12] showed that a transgenic protein, human growth hormone (hGH), secreted into the bloodstream could be biologically active. Subsequently, many additional studies, e.g., [59] with human insulin and hGH; [60] with human IL-10; [13, 61], both with hEpo; [62] with human α-galactosidase 1 in a model of Fabry disease; [63] with human exendin-4 in a model of Type 2 diabetes, have consistently shown that transgenic proteins and peptides can be secreted systemically from salivary glands and lead to biological function and/or the correction of disease in animal models.…”
Section: Endocrine Applicationsmentioning
confidence: 99%